«¿Cómmo vos á ydo, el mi leal amigo?» Las preguntas sobre el estado del interlocutor en la diacronía del español - Zieliński, Andrzej (Studia Romanica Posnaniensia, 2025)
In this article we address the issue of the variation of questions aimed at the personal state sequences in the history of the Spanish language. With a primordial phatic function, they not only serve to reestablish social harmony between individuals who have not seen each other for a long time, but also to fill the social void that social relations abhor.